Migrant workers, 'modern slavery' and the politics of representation in Italian tomato production. Issue 4 (2nd October 2019) - Howard, Neil; Forin, Roberto
Abstract: This paper examines representational politics in relation to the production and marketization of Italy's 'red Gold', the tomato. It centres around three competing images. The first, hegemonic image is of a bucolic countryside, pushed by agro-capital and retail. A stereotypically 'fetishizing' image, it hides both labour and its exploitation. The second is its counter-hegemonic opposite, of a countryside seething with indignity, populated by exploited workers, and neglected by the state. Advanced by civil society, this image parallels many within mainstream 'modern abolitionism' and seeks to shame big business into pursuing a more ethical capitalism. In our view, it re-inscribes the (neo)liberal paradigm that is foundational to the exploitation it wishes to overcome. It also alienates many of the people it purports to depict. The third image is an ethnographic alternative to the first two and is drawn from our fieldwork with the farmers, migrant workers and labour-brokers responsible for tomato production in Foggia, Southern Italy. Complex and contradictory, it depicts living and working conditions that are bad, but better than the alternative, and workers who are exploited, but nevertheless understand themselves as consenting to their exploitation.